Isolation, characterization and identification of plant growth-promoting rhizobacteria from the rhizosphere of Acacia mangium at sandy BRIS soil - Mustapha, Zakiah; Othman, Radziah; Nik Muhammad Nasir, Nik Nurnaeimah; Zawawi, Dhiya Dalila (Higher Education Press Limited Company, 2024)
This study has isolated, characterized, and identified potential plant growth-promoting rhizobacteria (PGPR) with multiple PGP characteristics (N2-fixation, P- and K-solubilization, IAA, and siderophores production) from the rhizosphere BRIS soil of Acacia mangium. A total of 24 pure colonies were isolated and only 8 colonies were selected for further evaluation of the growth rate in 5% organic molasses medium supplemented with 2% KNO3. Based on the biochemical, potential PGP characteristics and growth performance, 3 superior PGPR strains were selected and identified as Paraburkholderia unamae (UA1), Bacillus amyloliquefaciens (UA6), and Enterobacter asburiae (UAA2) by partial sequencing of the 16S rRNA gene. The selected bacterial strains either in single or mixed (UA1 + UA6 + UAA2) cultures have shown a significant biochemical estimation of the PGP characteristics. Each strain has its own PGPR traits superiority with UA1 showing the best PGP characteristic followed by UA6 and UAA2. The use of mixed bacterial strains was beneficial as it showed the best performance in N2-fixation, siderophores production, and significant effect on corn phenology, growth and yield compared to using a single strain. These types of microbes showed potential to be used as biofertilizer and should be exploited more.